The practice of time management by Debre Markos college of teacher education students: Multitasking, procrastination, task prioritization, and technology use - Atalay Mesfin; Melaku Mengistu Gebremeskel (College of education, Bahir Dar University, 2023)
This study attempted to examine the time management practices of students and the state of different factors of time management (multitasking, procrastination, task prioritizing, and technology use) at Debre Markos College of Teacher Education. Based on students' problem of meeting deadlines to properly carry out and submit assignments, students' time management practices, the status of the factors described, and differences among students based on sex and field of study regarding those factors were examined. The study employed descriptive survey design of the quantitative approach involving 113 students selected through a proportional simple random sampling technique. Questionnaire data were analyzed through mean, one sample t-test, independent samples t-test, and analysis of variance. Findings unveiled that students were not good enough in their time management practices. Paradoxically most students were multitasking, using technology, and procrastinating on the one hand and prioritizing their tasks, on the other. Although they do not have significant differences in their task prioritization, female students were more procrastinating than their male counterparts in their academic tasks. More male students than females were multitasking and using technology. Although patterns of moderate differences were observed in terms of fields of study, the statistical outputs imply that there were lots of variances among students both in their practice of procrastination and technology use.